(untitled) (Economic and Political Thought, 2020)
The main goal of this research is to discover the relation between the US–Mexico bilateral trade and the US industrial production, where the presidency of Donald Trump is treated as an exogenous factor. The paper is going to uncover some of the empirical studies, where economists estimate the productivity growth under different barriers to trade. With the use of the VAR model based on time series data, the impact of trade openness on productivity growth was assessed. The US industrial output during the period from 1985 to 2018 was taken as a sample for the purpose of analysis. Control variables, such as proxies of the aggregate production function, were also taken into consideration. Numerous pre-estimation and post-estimation tests were conducted in order to assess the reliability of the constructed model. In accordance with the results, the VAR estimations proved that there is a significant impact of Trump’s trade policies towards Mexico on the US industrial production.